Chemical composition of essential oils and comparative analysis of enzyme inhibitory, antioxidant and antimicrobial activities in essential oils of endemic Gelasia sericea (Aucher ex DC.) Zaika, Sukhor. & N. Kilian - Fidan, Muhammed Said; Baltaci, Cemalettin; Akmese, Osman; Sefali, Abdurrahman; Aygul, Imdat; Oz, Mehmet (Taylor & Francis Ltd, 2025)
In this study, essential oil from the aerial parts of Gelasia sericea (Aucher ex DC.) Zaika, Sukhor. & N. Kilian was extracted via hydrodistillation using a Clevenger apparatus. GC-MS/FID analysis determined aldehydes (28.31%) as the dominant group, with eucalyptol (8.71%) as the main constituent. Antioxidant activities were exhibited using DPPH, ABTS, and FRAP assays, with the essential oil demonstrating relatively higher antioxidant properties. The essential oil also showed higher levels of bioactive components, including total antioxidant capacity (160.26 mg AA eq./100 mL), total phenolic content (21.57 mg GA eq./100 mL), and total flavonoid content (14.85 mg QE eq./100 mL). While G. sericea essential oil demonstrated some antioxidant activity, it was significantly lower compared to the reference standard ascorbic acid (AA). The antimicrobial results showed relatively higher antimicrobial activity compared to most bacterial and fungal strains, as evidenced by lower MIC and MBC values and larger inhibition zones. Nevertheless, chloramphenicol (CH) and nalidixic acid (NA) continually showed superior antimicrobial efficacy, with the lowest MIC and MBC values and the largest inhibition zones. The essential oil also demonstrated potent enzyme inhibitory activity, especially against CA-II, AChE, and BChE, with the lowest IC50 value observed for CA-II, highlighting its potential as a potent enzyme inhibitor. However, the essential oil exhibited comparatively greater inhibition against AChE, BChE and alpha-amylase but was less effective overall. These findings suggest that the G. sericea essential oil has important antioxidant potential and enzyme inhibitory activity, while the essential oil shows varying efficacy across different enzymes.
Keywords: Antioxidant and antimicrobial activities; Chemical composition; Enzyme inhibition; Essential oil; Gelasia sericea